Influence of Heat Treatment on Biocorrosion and Hemocompatibility of Biodegradable Mg-35Zn-3Ca Alloy - Jeong-Hui Ji; Il-Song Park; Yu-Kyoung Kim; Sook-Jeong Lee; Tae-Sung Bae; Min-Ho Lee (Advances in Materials Science and Engineering)
Mg-35Zn-3Ca (wt.%) alloy containing nontoxic and biocompatible Zn and Ca as alloying elements was prepared and subjected to heat treatment and artificial aging for different duration of time to reduce its rate of degradation. Solution heat treatment was performed at 310°C while artificial aging was performed at 170°C for 0, 2.5, 5.0, 7.5, and 10.0 h and they were designated as AT0, AT1, AT2, AT3, and AT4, respectively. The finest and most homogenous reticulum was observed on the surface of the AT2 group. The result of immersion test in Hank’s balanced salt solution (HBSS) showed that the corrosion rate of the AT2 group was 2.32 mg/(cm2 day), which was significantly lower as compared to other groups P<0.05. The hemolysis value was ≤5% in all groups, indicating no toxicity during short-term blood reaction.